Um barco esquecido na praia: arqueologia e simbologia do barco da Galileia - Carvalho, Jane Viana Almeida de (2017)
The present work sought to develop a discussion about the Galilean ship. Discovered in 1986, on the shores of Lake Galilee, and dating to the first century D.C. It represents the first information of vessels from this period arising from material culture, for until then, the theme was present only in the biblical texts of the New Testament. In this way, the finding allowed a symbolic discussion about elements present in religious narratives because they presented different meanings. In this context, we seek to initiate an archaeological and symbolic analysis of this boat as nautical artefact, seeking to understand the different symbologies that surround it.